Title: Comparing the quality of life of mothers with cerebral palsy children based on walking ability - Zahra Ahmadizadeh; Mehdi Rassafiani; Fatemeh Ehsani; Ali Hosseini (Vesnu Publications, 2014)
Introduction: Many of study show decrease of quality of life in mothers of children with cerebral palsy due to care activity of their child but the researchers less pay attention to the decrease of mother's quality of life in relationship with child-related factors like walking ability in children with cerebral palsy, so the aim of this study was toComparing the quality of life of mothers with cerebral palsy children based on walking ability Materials Methods: In this causal-comparativestudy that performed in 2011 in Tehran city where 60 mothers of children with cerebral palsy 4 to12 years old was participated. Quality of life was assessed with SF-36 questionnaire andchildren with cerebral palsy were evaluated 1 to 5 level of gross motor function classification system by occupational therapist. The Pearson correlation test and linear regression was performed to investigaterelationship between variables with SPSS. Results: 24 mothers of children without walking ability and 36 mothers of children withwalking ability was participated in this study.themother's age mean± SD was 02/6 ± 79/33 and children's age mean± SD was 71/2 ± 11/7. Results of data analysis between two groups of mothers were significantly different in overall score of quality of life, social function, physical function and general health. (P <0/05) Conclusion Mothers of childrenwithoutwalking ability reported long care hours to and also have lower quality of life.   Keywords: Cerebral palsy, Quality of life, Mothers of children with cerebral palsy